Peronospora stigmaticola Raunk. – new species of pseudofungi in mycobiota of Belarus - Khramtsov, Alexander K. (Experimental Biology and Biotechnology, 2018)
The data concerning the first findings of the micromycetes Peronospora stigmaticola Raunk. (Peronosporaceae, Peronosporales, Oomycetes, Oomycota, Chromista) within Belarus is presented. This species is an obligate parasitic pseudofungus and causes downy mildew on the plants of the genus Mentha L. and Satureja L. Sporulation is formed only on the flowers of the host-plants. We supply data about distribution of this micromycetes, its chorologic features, host-plants and symptoms of downy mildew on flowers. Micromycetes P. stigmaticola is found on the flowers of Mentha spicata L. in the one location of Belarus. We provide a brief morphological description of this pathogen based on the assessing of collected samples. The herbarium samples that are referred to in our work and serve as the grounds for this article are retained in Belarusian State University Herbarium (MSKU). The results of this research work extend our knowledge of morphometric characteristics and distribution of pseudofungus P. stigmaticola and might be taken into consideration when compiling the inventory of mycobiota of Belarus. The information about possible host-plants P. stigmaticola in Belarus is valuable for the detection of diseased plants and development of measures for protection cultivated plants of the genus Mentha L. and Satureja L. from downy mildew of flowers.
Keywords: micromycetes Peronospora stigmaticola; pseudofungus; downy mildew; flowers; Mentha spicata; hostplants; mycobiota; Belarus